Illuminating dulaang laboratoryo's dalawang palabas ng kamatayan navigating the sign-object-interpretant in lights design - Rivera, Maria Loren C. (College of Arts and Letters, University of the Philippines Diliman, 2019)
This creative project was about describing and analyzing the processed involved in designing the lights for the Dulaang Laboratoryo's thesis production BALINTUNA: dalawang Palabas ng Kamatayan a production featuring Baliktanaw and Ang Seremonya. Focused on the process of conceptualization, this employs Charles Sanders Pierce's sign-object-interpretant triad as an approach. The 'Signs were the two plays featured; 'Objectives' were the initial script analysis, interpretation of research and production team's creative input; and 'Interpretants' were the final lights design concept, actual lights design during shows and observations of the Lighting Designer- Operator as the third interpretant. Lights design concepts were executed through the techniques lerned through experiences in lighting design and lighting design references in lighting a traverse stage. this project presented in four parts: 1. Presentation of the lights design process from conceptualization employing Pierce's sign- object- interpretant triad; 2. Technical techniques used in the production; 3. Analysis of the actual lights designs during the show and 4. Description of the design process employed for each play. This project primarily concludes that navigating through the sign- object-interpretant as an approach in conceptualization greatly helped the process of light design.